An assessment of interactions between global health initiatives and country health systems - Badara Samb (2018)
© 2009,Lancet Publishing Group. All rights reserved. Since 2000,the emergence of several large disease-specific global health initiatives (GHIs) has changed the way in which international donors provide assistance for public health. Some critics have claimed that these initiatives burden health systems that are already fragile in countries with few resources,whereas others have asserted that weak health systems prevent progress in meeting disease-specific targets. So far,most of the evidence for this debate has been provided by speculation and anecdotes. We use a review and analysis of existing data,and 15 new studies that were submitted to WHO for the purpose of writing this Report to describe the complex nature of the interplay between country health systems and GHIs. We suggest that this Report provides the most detailed compilation of published and emerging evidence so far,and provides a basis for identification of the ways in which GHIs and health systems can interact to mutually reinforce their effects. On the basis of the findings,we make some general recommendations and identify a series of action points for international partners,governments,and other stakeholders that will help ensure that investments in GHIs and country health systems can fulfil their potential to produce comprehensive and lasting results in disease-specific work,and advance the general public health agenda. The target date for achievement of the health-related Millennium Development Goals is drawing close,and the economic downturn threatens to undermine the improvements in health outcomes that have been achieved in the past few years. If adjustments to the interactions between GHIs and country health systems will improve efficiency,equity,value for money,and outcomes in global public health,then these opportunities should not be missed.